"Shirley, Bernstein Can't Be Serious?": Airplane! and Compositional Personas. (12th January 2015) - Summers, Tim
Abstract : Elmer Bernstein describes that when he scored the comedy film Airplane! (1980), he "made up a role for the composer", a "young, inexperienced composer composing th[e] score". This article explores the notion of a scoring persona by examining how Bernstein not only deploys the persona in Airplane!, but also how he demonstrates that it is an insincere persona. The majority of the article analyses how Airplane!'s score, by using the compositional persona, satires film music, creates humor through the parodic music, and even seems to serve a pedagogical function. Airplane! highlights the issue of authorship in music for moving-image media and the article then suggests that audiences can understand film scores in terms of personas (whether or not intentionally, or consciously, deployed by the composers) and that understanding the work and impact of such personas is valuable for film music practitioners and analysts.